A UV-Visible spectrophotometric approach to quantify caffeine and carbohydrates in Dhaka's chocolate and candy selection, Bangladesh - Islam, Md. Mazharul; Tanjid, Sanjida; Shoeb, Mohammad (The North African Journal of Food and Nutrition Research, 2025)
Background: Caffeine and carbohydrates are significant components in chocolate and confectionery products, influencing both their sensory appeal and health impact. Accurate quantification of these components is essential to provide consumers with reliable nutritional information and to inform healthier dietary choices.Aims: This study aims to quantify the moisture and ash content, as well as determine the concentrations of caffeine and carbohydrates, using UV-Visible spectrophotometry, in selections of chocolates and candies commercially available in Dhaka, Bangladesh. Additionally, the study seeks to elucidate variations in these components across different brands and product types, thereby contributing to a better understanding of their compositional profiles.Methods: Samples from six chocolate brands and two coffee candy brands were procured from local markets and supermarkets in Dhaka. Standard analytical methodologies were employed to determine moisture and ash content. For the quantification of caffeine and carbohydrates, standard solutions were prepared, and absorbance measurements were conducted using a UV-Visible spectrophotometer at specified wavelengths. Moisture and ash content were calculated using standard formulas, while caffeine and carbohydrate concentrations were derived from calibration curves.Results: The moisture content in the analyzed samples ranged from 0.25% to 1.88%, while ash content varied between 5.22% and 6.90%. Caffeine concentrations were found to range from 24.18 ± 2.51 mg.kg-1 in Perk chocolate to 60.12 ± 0.85 mg.kg-1 in KitKat (70% Dark). Carbohydrate content exhibited considerable variation, with values ranging from 2.03 ± 0.01 g/100 g in Coffee Bite to 41.05 ± 0.46 g/100 g in Perk chocolate per 100 g. Dark chocolate samples demonstrated higher caffeine levels compared to milk and white chocolate varieties, consistent with their elevated cocoa solid content.Conclusions: The study revealed significant variability in moisture, ash, caffeine, and carbohydrate content across different chocolate and candy brands. These findings emphasize the necessity of rigorous compositional analysis for quality assurance and public health considerations.Keywords: Caffeine, Carbohydrates, Chocolate, Candy, UV-Visible Spectrophotometry.